Optimasi Pariwisata Kreatif Berbasis Integrasi Potensi Lokal Desa Puntukrejo Untuk Mewujudkan Sustainable Development Goals Desa - Aldi Rizki Khoiruddin; Muhammad Ainurrasyid Al-Fikri; Aditya Tri Wijaya; Alizza Khumaira Assyifa; Jelita Kristi Agape; Ika Putri Wijayanti; Hanif Alwa Mumtaz; Petrus Kanisius Eko K; Ragil Listyaningrum; Widyasari Rizki Ananda; Yusriel Bachrie; Muhammad Rustamaji; Rysca Indreswari (Unri Conference Series: Community Engagement, 2021)
The lack of innovation and creativity causes many tourist destinations during this pandemic to have no distinction from other tourist destinations. Though there are many opportunities from the village that can be developed and then integrated between each other to support the peculiarities of a region. The same is true of PuntukrejoVillage. Puntukrejo Village which is the main access to the entrance to Ngargoyoso District offers a variety of natural and cultural tourist destinations. Puntukrejo village has one of the preferred tourist destinations, namely The Lawu Fresh which is an agrotourism pioneer cultivating dekopon oranges, honey gourds, bottled pumpkins, and vegetables. However, since the pandemic, the number of tourist visits at The Lawu Fresh has dropped dramatically. This is due to the lack of innovation made by the village in developing the tourist village. Therefore, the service team in collaboration with partner villages aims to make creative tourism innovations in the form of Educative and Creative Camping with the concept of Indian Night, improve the marketing system of Puntukrejo Village's Flagship MSME products, and realize the existence of MSMEs with dual roles as production centers and destinations in the Jeep Adventure travel package series. The method of community empowerment used in this devotional activity is Participatory Rural Appraisal (PRA). Methods that apply the active role of partner villages together with service teams in developing village potential. The result of this devotion is the rise of community skills in marketing tourist attractions and MSME products owned by the village through various social media such as Instagram, Tiktok, Facebook, and Youtube. This skill increase goes hand in hand with the increasing number of tourists who come to village tourist attractions, as well as also buying village MSME products.